Factors Contributing to Drug Release From Enteric-Coated Omeprazole Capsules: An In Vitro and In Vivo Pharmacokinetic Study and IVIVC Evaluation in Beagle Dogs - Cheng Cui; Jiabei Sun; Xueqing Wang; Zhenxi Yu; Yaqin Shi (SAGE Publishing, 2020)
This study was performed to explore factors influencing the release of the proton pump inhibitor omeprazole from enteric-coated capsules in vitro and absorption in vivo in beagle dogs. Enteric-coated pellets with different enteric coating materials and coating levels were designed and prepared. All self-prepared formulations were characterized in vitro as well as in vivo and compared to the brand and generic commercial products. Evaluation of the corresponding release profiles suggested that coating material was the most critical factor. Enteric coating level determined the lag time before initiation of drug release, and subcoating level affected the drug release rate. Pharmacokinetic studies were performed in beagle dogs to further confirm the influence of formulation factors on drug absorption. Medium at pH 6.8 was a more biorelevant condition for in vitro drug release tests, although medium at pH 6.0 was better for discriminating release profiles of different formulations. A multiple level C in vitro/in vivo correlation was preliminarily established by which T max and C max of omeprazole formulations could be predicted with release parameters such as T lag and T 25 . These results may facilitate quality evaluation and potentially improve the clinical efficacy of generic omeprazole products.